National Character Development and Cultural Education from a Local Wisdom - Thresia, Fenny; Sinaga, Risma Margaretha; Adha, Muhammad Mona (PPSDP International Journal of Education, 2024)
In this qualitative study, we would like to discover the national character development and cultural education from a local wisdom. The results obtained indicate that Indonesian national education today still faces a number of significant problems. The educational outcomes have not met the expected expectations, in which the learning process in schools is still unable to form the integrity of the graduates and reflect the character and culture of the nation. The education process tends to focus on the cognitive aspects, while the affective aspects that are essential for living in society have not been optimally developed. Therefore, the development of the education of the character and culture of the nation has become a must to be done in schools. Schools as the centre of change must pursue education based on the character and culture of the nation with seriousness. The character and the culture of a nation developed in the school must be in harmony with the local, regional, and national character and cultures. To these goals, the education of character and cultural nation must be developed based on local wisdom.